PRONUNCIATION LEARNING, PARTICIPATION, AND ATTITUDE ENHANCEMENT THROUGH MOBILE ASSISTED LANGUAGE LEARNING (MALL) - Alfi Hidayatu Miqawati (English Review: Journal of English Education, 2020)
: A mobile application, Tflat English Pronunciation, is proposed in the teaching of pronunciation for it possesses features that can assist students when learning how to enunciate English words and identify English phonemic symbols.  Thus, this study presents the results of the implementation of Tflat English Pronunciation mobile courseware to gain the ability of the first semester students of English Study Program Politeknik Negeri Jember in pronouncing English words. This study is a collaborative classroom action research. Thirty students enrolling in Pronunciation class at English Study Program Politeknik Negeri Jember were taken as the source of data. The result showed that the materials and practices in Tflat courseware could enrich students' pronunciation learning, improve their participation, and nurture a positive attitude toward technological learning. The findings of this study also depict the potential and power of Mobile Assisted Language Learning (MALL) to encourage students to engage in classroom activities and monitor their learning. Hence, it can be concluded that MALL is pivotal and can be one alternative to facilitate students’ pronunciation learning.